Sustainable utilization of biowaste compost for renewable energy and soil amendments. (December 2020) - Chia, Wen Yi; Chew, Kit Wayne; Le, Cheng Foh; Lam, Su Shiung; Chee, Chelsea Siew Chyi; Ooi, Mae See Luan; Show, Pau Loke
Abstract: Acceleration of urbanization and industrialization has resulted in the drastic rise of waste generation with majority of them being biowaste. This constitutes a global challenge since conventional waste management methods (i.e., landfills) present environmental issues including greenhouse gases emissions, leachate formation and toxins release. A sustainable and effective approach to treat biowaste is through composting. Various aspects of composting such as compost quality, composting systems and compost pelletization are summarized in this paper. Common application of compost as fertilizer or soil amendment is presented with focus on the low adoption level of organic waste compost in reality. Rarely known, compost which is easily combustible can be utilized to generate electricity. With the analysis on critical approaches, this review aims to provide a comprehensive study on energy content of compost pellets, which has never been reviewed before. Environmental impacts and future prospects are also highlighted to provide further insights on application of this technology to close the loop of circular bioeconomy. Graphical abstract: Image 1 Highlights: Conversion of waste to compost can reduce environmental pollution of organic waste. Composting process, compost quality and composting systems are critically reviewed. Compost can be utilized as fertilizer and energy fuel, promoting circular economy. Production and combustion of compost fuel have high efficiency of energy recovery. Optimizing composting process and composter can mitigate the environmental impacts. Abstract : This paper reviews composting process and utilization of compost for fertilizer and bioenergy to reduce waste volume, mitigate pollution and promote circular bioeconomy.